Synthesis routes to eliminate oxide impurity segregation and their influence on intergrain connectivity in K-doped BaFe2As2 polycrystalline bulks. (13th July 2020) - Pak, C; Su, Y F; Collantes, Y; Tarantini, C; Hellstrom, E E; Larbalestier, D C; Kametani, F
Abstract: The poor reproducibility of intergrain critical current density Jc in Fe-based superconductors is often believed to result from uncontrolled grain boundary (GB) connectivity degraded by extrinsic factors such as the local or global impurity concentration or GB porosity or cracks. Earlier we found that Ba and K can appear as oxide impurities at GBs, along with GB-wetting FeAs. In this study, we evaluated how the sample preparation environment and purity of the starting materials influence the polycrystalline Jc in K-doped BaFe2 As2 (Ba122) bulks. Using a high-performance glovebox, the oxygen and water levels were significantly reduced, eliminating traces of FeAs. Oxide impurities and Ba (or K) segregation associated with oxygen in the starting materials were significantly reduced by using high purity starting materials. This combination essentially doubled the best Jc (4.2 K) values to 2.3 × 10 5 at self-field and 1.6 × 10 4 A cm −2 at 10 T and analytical scanning transmission electron microscopy showed no GB or O segregation in the best samples, but did show dark Z-contrast and distinct nanoscale porosity. Our work shows that an inert synthesis environment and high purity K and Ba do reduce current-blocking oxygen impurity and GB impurity phases, allowing deeper exploration of the role of extrinsic and intrinsic GB blocking effects in controlling the Jc of polycrystalline Ba122.